2014
DOI: 10.1242/dev.105270
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 controls the number and distribution of astrocytes and oligodendrocytes in the gray matter and white matter of the spinal cord

Abstract: Glia constitute the majority of cells in the mammalian central nervous system and are crucial for neurological function. However, there is an incomplete understanding of the molecular control of glial cell development. We find that the transcription factor Ascl1 (Mash1), which is best known for its role in neurogenesis, also functions in both astrocyte and oligodendrocyte lineages arising in the mouse spinal cord at late embryonic stages. Clonal fate mapping in vivo reveals heterogeneity in Ascl1-expressing gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 51 publications
8
39
0
Order By: Relevance
“…As previously reported (Parras et al, 2007; Sugimori et al, 2007; Sugimori et al, 2008; Vue et al, 2014), immunofluorescence for ASCL1 showed that it is highly expressed in glial progenitors and precursor cells that span the dorsal-ventral extent of the spinal cord at E14.5 (Fig. 1A).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…As previously reported (Parras et al, 2007; Sugimori et al, 2007; Sugimori et al, 2008; Vue et al, 2014), immunofluorescence for ASCL1 showed that it is highly expressed in glial progenitors and precursor cells that span the dorsal-ventral extent of the spinal cord at E14.5 (Fig. 1A).…”
Section: Resultssupporting
confidence: 86%
“…Statistical analyses were performed as previously described (Vue et al, 2014) to assess the differences in NG2-glia cell density or percentage expression of marker+;tdTOM+ cells in GM and WM between control and Ascl1 -CKO. In short, a linear regression technique to model the observed cell number as a linear combination of fixed effect (genotype) and random effect (animal ID) was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher KL levels in CC and lower levels in spinal cord imply that KL needs and functions may differ between these regions of the CNS and could explain the different effects of KL overexpression in the cuprizone and EAE models. For example, the conditional deletion of the transcription factor Ascl1 (Mash1) postneurogenesis shows that Ascl1 is required during oligodendrogenesis for generating the correct numbers of white matter, but not gray matter OPCs, suggesting that these cells are not created equally (Vue et al 2014). Also, mTOR was shown to be necessary for proper OL differentiation and myelination in the spinal cord, but not in the cortex.…”
Section: Discussionmentioning
confidence: 99%